INDEKS KESESUAIAN WISATA DAN DAYA DUKUNG KAWASAN WISATA WADUK GONDANG, KABUPATEN LAMONGAN - Fuquh Rahmat Shaleh; Norma Aprilia Fanni; Nuralim Pasisingi (University of Prof. Dr. Hazairin, SH, 2022)
Gondang Reservoir is one of the main tourist destinations in Lamongan Regency. Utilization of water tourism in Gondang Reservoir is still not optimal due to lack of data on tourist sustainability and the carrying capacity of the right water tourism area. This research aims to find out the appropriate tourism activities and get the carrying capacity of the tourist area in Gondang Reservoir as a foundation for tourism development in the right reservoir, sustainable and sustainable in the creation of community welfare. The method used is a descriptive method with a quantitative approach. This study analyzed the tourism suitability index and the carrying capacity analysis of tourist areas. The results showed that the tourist activities that are very suitable in Gondang Reservoir are boat tours, relaxing and camping while for fishing and outbound activities the category is appropriate. The ability to carry the gondang reservoir to accommodate the activities of the 5 tours as many as 990 people / day or 361,185 people / year.